Estimation of energy recovery potential and environmental impact of Tirana landfill gas - Alcani, Majlinda; Dorri, Altin; Maraj, Altin (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
Due to a very high percentage of organic matter in municipal solid waste (47.36%) and in total percentage of biodegradable matter (62.3%), organic waste disposed is the main source of methane emissions into the air in Albania. Capture, collection and utilization of landfill gas in an energy project leads to economic, health and environmental benefits. Energy recovery potential and methane emissions from Tirana landfill have been studied. This site is scheduled to be closed after 6 or 7 years. The evaluation has been done using LandGEM Colombia Model, version 1.0, as an international LFG Modeling. The model predicted the time of peak production in 2019, one year after assumed site closure. The total annual peak of predicted methane recovery from landfill within the study time frame was estimated to be 2950 m3/h and a maximum of power plant capacity 8.3 MW.
Environment Protection Engineering. Vol. 44, 2018, nr 3, s. 117-128
Keywords: ochrona środowiska; czasopisma; inżynieria środowiska